2018
DOI: 10.1088/2053-1591/aaa678
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of periodic nanovoid structures in Mg single crystals

Abstract: Abstract. Large scale molecular dynamics (MD) simulations in Mg single crystal containing periodic cylindrical voids subject to uniaxial tension along the z direction are carried out. Models with different initial void sizes and crystallographic orientations are explored using two interatomic potentials. It is found that (i) a larger initial void always leads to a lower yield stress, in agreement with an analytic prediction; (ii) orientations, the two potentials identically predict the nucleation of edge dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As typical HCP materials, magnesium and magnesium alloys have been widely used in the aerospace, automobile, defense, and medical fields due to their excellent properties of low density and high strength [22][23][24]. In practical engineering materials, the effects of unavoidable or artificial defects, such as voids [25][26][27][28], cracks [29], grain boundaries [30,31], and dislocations [32], on the plasticity of Mg materials, have received extensive attention. For example, Li et al [28] revealed two typical void collapse mechanisms of nanoporous magnesium under shock loading by MD simulations: the plasticity mechanism and the internal jetting mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…As typical HCP materials, magnesium and magnesium alloys have been widely used in the aerospace, automobile, defense, and medical fields due to their excellent properties of low density and high strength [22][23][24]. In practical engineering materials, the effects of unavoidable or artificial defects, such as voids [25][26][27][28], cracks [29], grain boundaries [30,31], and dislocations [32], on the plasticity of Mg materials, have received extensive attention. For example, Li et al [28] revealed two typical void collapse mechanisms of nanoporous magnesium under shock loading by MD simulations: the plasticity mechanism and the internal jetting mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…25 We use an embedded-atom method potential 26 known to well describe the generalized stacking fault energies, which are important for plastic deformation mechanisms including dislocation slip and twinning. [27][28][29][30] The lattice parameter is 3.143 39 Å. In all simulations, an NPT ensemble and an NVT ensemble are applied, respectively, to the bulk single crystals and the NTs/NWs, with a constant time step size of 2 fs at 300 K. Each model initially undergoes a dynamic relaxation for 250 ps, followed by tensile deformation along the z direction with a constant engineering strain rate _ ε ¼ 10 8 s À1 .…”
Section: Methodsmentioning
confidence: 99%
“…24 As the validity of MD simulations considerably hinges on the choice of interatomic potential, it is crucial to employ an appropriate interatomic potential so as to attain accurate results. [25][26][27][28][29][30] Atomic interactions of SiC are modelled using the effective many-body interatomic potential developed by Vashishta et al, 31 which is capable of reasonably reproducing the generalized stacking fault energies, cohesive energy, elastic constants, and melting point of 3C-SiC. The initial nanocrystalline structure is generated using the Voronoi tessellated method.…”
Section: Simulation Methodologymentioning
confidence: 99%